2011
DOI: 10.1083/jcb.201010100
|View full text |Cite
|
Sign up to set email alerts
|

miR-22 represses cancer progression by inducing cellular senescence

Abstract: The microRNA miR-22 targets CDK6, SIRT1, and Sp1—genes involved in regulation of the senescence program—to suppress cell growth and proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
206
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(221 citation statements)
references
References 65 publications
(66 reference statements)
14
206
1
Order By: Relevance
“…MiR‐22 was initially defined as one of the senescence‐associated microRNAs that represses cancer progression by inducing cell senescence (Xu et al ., 2011). However, a subsequent analysis revealed that miR‐22 is most prominently upregulated during cardiovascular aging, targeting minecan (osteoglycin, OGN; Jazbutyte et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐22 was initially defined as one of the senescence‐associated microRNAs that represses cancer progression by inducing cell senescence (Xu et al ., 2011). However, a subsequent analysis revealed that miR‐22 is most prominently upregulated during cardiovascular aging, targeting minecan (osteoglycin, OGN; Jazbutyte et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al indicated that miR-22 plays roles both in cell senescence and tumorigenesis (8): the expression of miR-22 is induced by cell senescence while it is reduced in various malignant tumor cells. The authors also indicated that overexpression of miR-22 suppresses the development of breast cancer in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results clearly demonstrate that at least in CGNPs, miR-22 slows down the cell cycle progression but does not induce neuronal differentiation, indicating that the reported presence of miR-22 in various differentiating cell types does not necessarily imply a direct role of miR-22 in the differentiation process. Moreover, miR-22 has also been demonstrated to have a potent antiproliferative effect in differ-ent cancer cell lines (30) and to induce senescence in fibroblasts (32). Thus, given that compounds that promote differentiation or senescence exert their effects primarily on the cell cycle, miR-22 may reflect a common antiproliferative element working in different cellular processes whereby a slowdown in the cell cycle is required.…”
Section: Discussionmentioning
confidence: 99%